On the Funding Chances of Political Theorizing. - Rosales, José María (De Gruyter, 2024)
This article explores causes and consequences of the declining funding chances of political theorizing with the aim of advancing measures to offset them. Major national and international research programmes growingly present challenges that require problem-solving strategies. Applied research disciplines are better fitted to tackle them than basic research disciplines to which political theo- rizing belongs. Drawing on the enlightening contribution of theory to political research and politics, it argues that the knowledge it produces can be shared across disciplinary boundaries if its scientific reliability is secured. With that aim, the article submits two practical suggestions: enriching normative accounts of politics with research historically and institutionally informed, and streamlining its enquiring capacity by exploring standard, modular and integrated interdisciplinary approaches.
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/26603
Keywords: Filosofía política; Political theorizing; Philosophy and politics; Research funding; Research methodology; Interdisciplinary research